Perlindungan Hukum terhadap Konsumen Smartphone Bermerek Iphone dalam Pemblokiran International Mobile Equipment Identity (Imei) di Yogyakarta - Sinrang, Andi Rizqya Fitriany; Nugroho, Eko Rial (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This research aims to analyze the form of legal protection for consumers in the event of blocking the IMEI on the Iphone and analyze the liability of consumers in blocking the IMEI on the Iphone. The type of research used in this research is normative juridical research with a statutory approach and a case approach. The research data source uses secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research data collection technique in this research uses literature study and document study and the research data analysis method uses descriptive qualitative. The result of this research is the form of legal protection for consumers in the event of blocking of IMEI on i-phone is a form of preventive legal protection and repressive legal protection. Preventive legal protection to consumers is carried out by fulfilling consumer rights and fulfilling the obligations of business actors as regulated in Article 5, Article 7 and Article 8 paragraph (1) of the Consumer Protection Law, and Article 3 paragraph (1) Permenkominfo 1/2020. Forms of repressive legal protection through dispute resolution efforts with non-litigation legal steps and litigation legal steps. The liability of business actors to consumers on smartphones with unregistered IMEI is that the business actor (seller), namely the “Tepat Store” Store, provides compensation for damage and / or loss to consumers as a result of using the goods being traded in the form of a refund in the amount of the selling price of the goods purchased by the buyer (consumer), which is Rp. 6,729,000, 00 (six million seven hundred twenty-nine thousand rupiah). The buyer (consumer) is asked to return or surrender the smartphone that has been purchased to the seller with a reset condition.